A STYLISTIC ANALYSIS OF THE THREE DREAMS IN EARNEST HEMINGWAY’S “THE OLD MAN AND THE SEA” - Thiab , Ahlam Abdulrazzaq (International Journal of Psychosocial Rehabilitation, 2025)
The topic of this research is “A Stylistic analysis of the Three Dreams in Earnest Hemingway’s "The Old Man and The Sea." This research describes the stylistic analysis of the imageries and expressive means used in this novel to reveal the insides and the role of the hero through his dreams. These dreams represent the adjustments in the mind that are linked to sleep. The devices used along with the images and expressive means play a philosophical, sociological and psychological mirror of what is hidden inside the hero’s mind and psyche and what is beyond the power of dreams in fiction. In this research, we introduce all the images, which demonstrate various symbols in the hero’s life and in his hard society, which in turn characterize the individual style of the author. Dreams function effectively in simulating threats, handling both of the emotional and intellectual problems, and reinforcing memories for the author.